On the Characteristic Operator of an Integral Equation with a Nevanlinna Measure in the InЇnite-Dimensional Case - Bruk, V.M. (Журнал математической физики, анализа, геометрии, 2014)
We define the families of maximal and minimal relations generated by an integral equation with a Nevanlinna operator measure in the infinite-dimensional case and prove their holomorphic property. We show that if the restrictions of maximal relations are continuously invertible, then the operators inverse to these restrictions are integral. By using these results, we prove the existence of the characteristic operator and describe the families of linear relations generating the characteristic operator.